Marketing Knowledge Management Analysis to Drive Innovation and Effective Decision Making - Haris, Abdul (Advances in Business & Industrial Marketing Research, 2025)
Purpose: This study explores the strategic role of knowledge management (KM) in driving innovation and supporting effective marketing decision-making. By examining the integration of advanced technologies such as artificial intelligence (AI), machine learning (ML), and big data analytics, this research addresses the intersection of KM, innovation, and strategic marketing practices to provide actionable insights for organizations. Research Design and Methodology: The study employs a systematic literature review (SLR) approach to synthesize existing research on KM's application in marketing. It analyzes peer-reviewed journals and scholarly articles published after 2018 to identify patterns, challenges, and opportunities. The analysis focuses on bridging theoretical frameworks with practical applications to reveal KM's transformative potential in modern marketing. Findings and Discussion: The research highlights KM's capacity to transform raw data into actionable insights, enabling organizations to anticipate consumer needs, adapt to dynamic market changes, and develop innovative strategies. It also identifies the critical role of collaboration, leadership, and organizational culture in ensuring KM's effectiveness. Additionally, the study discusses challenges such as resistance to change and the need for digital infrastructure and training. The findings emphasize the synergistic relationship between KM and digital technologies in fostering sustainable competitive advantage. Implications: This research provides practical guidance for organizations to enhance marketing performance through KM. It recommends investing in advanced technologies, cultivating a knowledge-sharing culture, and fostering leadership-driven initiatives. These strategies can drive innovation, improve decision-making, and ensure organizational sustainability in competitive markets.